Development of High Fat Diet-Induced Hyperinsulinemia in Mice Is Enhanced by Co-treatment With a TLR7 Agonist - Kakalij, Rahul M.; Dsouza, Del L.; Boesen, Erika I. (Frontiers in Physiology, 2022)
Metabolic syndrome (MetS) is common in Systemic Lupus Erythematosus (SLE) patients and is associated with increased cardio-renal risk. Toll-like receptor 7 (TLR7) stimulation promotes the development of SLE through mechanisms including activating type I Interferon (IFN) and autoreactive B cells. The current study tested whether combined TLR7 agonist treatment and exposure to a high fat, high sucrose “Western diet” intervention affects the early-stage development of SLE or MetS features. Female C57BL/6 mice were untreated or treated with the TLR7 agonist imiquimod (IMQ) and fed a high-fat diet (HFD; fat 42% kcal, sucrose 34% kcal) or control diet (fat 12.6% kcal, sucrose 34% kcal) for 6 weeks. Supporting early-stage induction of autoimmunity, spleen weights were significantly increased and anti-nuclear antibody (ANA) positivity was detected in IMQ-treated mice. Increased body weight, gonadal fat pad mass, and plasma leptin levels were observed between HFD and control animals for both IMQ and untreated mice. However, the increase in these parameters with HFD was slightly but significantly diminished in IMQ-treated mice. Both the HFD and IMQ treatments significantly increased fasting blood glucose levels. Notably, IMQ treatment affected fasting insulin concentrations in a diet-dependent manner, with hyperinsulinemia observed in IMQ-HFD treated mice. Together, this indicates that the IMQ model of SLE is associated with metabolic alterations, impaired glycemic control, and hyperinsulinemia under HFD conditions. This model may be helpful in further investigating the relationship between MetS and SLE, and supports a role of TLR7 signaling in promoting or accelerating the development of dysglycemia and hyperinsulinemia.